TEGANGAN PEMULIHAN PADA KONTAK PEMUTUS DAYA TEGANGAN TINGGI UNTUK PROTEKSI TERHADAP GELOMBANG BERJALAN - Ikbal, Muhamad (Jurnal Qua Teknika, 2018)
In general we have known the frequent disruption of transmission lines is a natural disturbance, such as lightning disturbance to the transmission network due to transmission network through the air, long, high and spread in various open areas and operate in all kinds of conditions. Among the considerations taken in the transmission line transmission design is the location of the ground wire against the phase wire. Because the ground wire only, so a small percentage on the phase wire. And until now there are no scholars who show the use of lightning for life, have not got a way to prevent or exploit the energy caused by the lightning. Nevertheless, human science continues to thrive with technological advances. With one safety device, an air wire (Overhead Ground Wire) to protect the phase wires from the transmission line.